Pharmacogenomics Revolution: From Genetic Insights to Personalized Medicine (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Pharmacogenomics, at the intersection of genomics and pharmacology, is revolutionizing personalized medicine by exploring how genetic variations influence individual drug responses. Recent advancements include the integration of pharmacogenomic data into electronic health records and the development of gene-based diagnostics for predicting treatment efficacy and safety. Expanding research across diverse populations helps address genetic variability and reduces healthcare disparities. Cutting-edge technologies like next-generation sequencing and CRISPR are accelerating the identification of actionable genetic variants. However, challenges such as high testing costs, ethical implications, and the need for greater awareness among healthcare providers remain. Despite these hurdles, pharmacogenomics is rapidly advancing toward becoming a cornerstone of precision healthcare, optimizing therapeutic outcomes for patients worldwide.
Keywords: Pharmacogenomics; Personalized Medicine; Genetic Variability; CRISPR; Drug Response